General Anesthesia Causes Epigenetic Histone Modulation of c-Fos and Brain-derived Neurotrophic: Factor, Target Genes Important for Neuronal Development in the Immature Rat Hippocampus. Issue 2 (June 2017) - Dalla Massara, L.; Osuru, H.P.; Oklopcic, A.; Milanovic, D.; Joksimovic, S.M.; Caputo, V.; DiGruccio, M.R.; Ori, C.; Wang, G.; Todorovic, S.M.; Jevtovic-Todorovic, V.
Abstract : ( Anesthesiology . 2016;124(6):1311–1327) Research studies have shown that general anesthesia (GA) exposure among young animals causes cognitive impairments in not only first generation offspring but also nonexposed second generation offspring born to dams. Studies on rodents have revealed that GA exposure in utero has proven this to be true, thus confirming that transient GA exposure during a critical period of neuronal remodeling does result in changes that become embedded in the genetic information thus causing cognitive impairments. This study hypothesized that during critical stages of synaptogenesis, transient exposure to GA results in epigenetic changes in chromatin with adverse effects on transcription of target genes which are important for proper synapse formation and cognitive development.